2010
DOI: 10.1111/j.1365-2249.2010.04167.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo manipulation of Vγ9Vδ2 T cells with zoledronate and low-dose interleukin-2 for immunotherapy of advanced breast cancer patients

Abstract: SummaryThe potent anti-tumour activities of gd T cells have prompted the development of protocols in which gd-agonists are administered to cancer patients. Encouraging results from small Phase I trials have fuelled efforts to characterize more clearly the application of this approach to unmet clinical needs such as metastatic carcinoma. To examine this approach in breast cancer, a Phase I trial was conducted in which zoledronate, a Vg9Vd2 T cell agonist, plus low-dose interleukin (IL)-2 were administered to 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
216
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(222 citation statements)
references
References 43 publications
6
216
0
Order By: Relevance
“…24 Currently, most clinical studies are aimed at increasing the cd T cell population in patients by administering certain phosphoantigens intravenously to expand cd T cells in vivo, or by adoptive transfer of self cd T cells stimulated with phosphoantigen in vitro. [6][7][8][9][10][11] We have previously established conditions for expanding peripheral blood cd T cells with immobilized anti-cd TCR antibodies over a 2-week culture period. 16 The in vitro-expanded cd T cells displayed potent cytotoxicity against various tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Currently, most clinical studies are aimed at increasing the cd T cell population in patients by administering certain phosphoantigens intravenously to expand cd T cells in vivo, or by adoptive transfer of self cd T cells stimulated with phosphoantigen in vitro. [6][7][8][9][10][11] We have previously established conditions for expanding peripheral blood cd T cells with immobilized anti-cd TCR antibodies over a 2-week culture period. 16 The in vitro-expanded cd T cells displayed potent cytotoxicity against various tumours.…”
Section: Discussionmentioning
confidence: 99%
“…6 In another clinical trial, in patients with advanced breast cancer treated with zoledronate and IL-2, a statistically significant correlation between clinical outcome and peripheral Vc9Vd2 T cell numbers emerged. 7 In addition, the direct transfer of in vitro-expanded cd T cells has been used in some clinical trials and was proven to be safe. [8][9][10] In a trial of adoptive transfer of in vitroexpanded cd T cells to non-small cell lung cancer patients, immunomonitoring data showed that the number of peripheral cd T cells gradually increased with increasing numbers of infusions.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, local access to inflamed tissues and draining lymph nodes in humans is very limited, thereby severely compromising investigations into the APC function of Vc9/Vd2 T cells -or, as a matter of fact, into the APC function of any human immune cell. Indirect support for a possible role as APC stems from observations that HLA-DR is expressed by activated Vc9/Vd2 T cells in patients with severe inflammation or during acute infection [123,[138][139][140], and in patients receiving intravenous zoledronate with and without IL-2 [65,141,142]. However, functional evidence into the potential of activated Vc9/Vd2 T cells to act as APC ex vivo is only beginning to emerge [123,143].…”
Section: Priming Of Cd4 + and Cd8 + T Cells By Vc9/vd2 T Cells: A Newmentioning
confidence: 99%
“…With results from three cd cell-responsive patients reaching either disease stabilization (two patients) or partial remission (one patient), the authors could correlate the clinical outcomes to blood cd T-cell numbers. 37 In France, using the synthetic phosphoantigen BrHPP (IPH1101), Bennouna and colleagues 38 conducted a phase I trial in 28 patients with solid tumors to determine the maximum-tolerated dose and safety of this drug when combined with low doses of IL-2. Patients received BrHPP alone (1 h i.v.…”
Section: Rationale For Harnessing CD Cells In Cancer Immunotherapymentioning
confidence: 99%